Improvement of Flexural Properties and Dimensional Stability of Rice Husk Particleboard Using Wood Strand from Azadirachta excelsa in Face Layer - Mohd Nazri Wan Abdul Rahman, Wan; Zahir Bin Nazri, Muhamad; Yuziah Mohd Yunus, Nor (International Journal of Engineering and Technology, 2018)
Improvement of flexural properties and dimensional stability of rice husk particleboard is targeted in this study. Hybrid boards utilizing Azadirachta excelseastrands at surface and rice husk as core was manufactured and tested.  Rice husk particleboardscontaining five percentage ratio of A.excelsea (0, 10, 20, 30 and 40%) were tested.Additional work was done with 40% A.excelsea content with random and aligned arrangement to observe effect of strands layout. The results showed significant (p ≤ 0.05) improvement in flexural strength (modulus of rupture, MOR and modulus of elasticity, MOE) as the face layer percentage increases. The dimensional stability (water absorption and thickness swelling) with 40% A.excelsea content showed the best performance. Arrangement of strand showed alignment improved MOE but internal bond, MOR and physical properties were not significantly affected. Overall there is potential to improve the flexural properties and dimensional stability with variation of strands percentages at face layer.